2018
DOI: 10.1002/met.1754
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall asymmetries of landfalling tropical cyclones along the South China coast

Abstract: The rainfall distribution associated with landfalling tropical cyclones (TCs) along the South China coast are examined using radar data from Hong Kong Observatory (HKO). This preliminary study relates the landfall direction, and possible rotations/transitions of TC rainfall asymmetries before and after the landfall. Three types of landfalling TCs on the South China coast are categorized: from the east, normal to the coast and from the southwest. For those from the east, the rainfall maximum rotates anticycloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Figure 2i-l show the rainfall distribution during the passage of sequential typhoons, and the maximum rainfall exceeded 200 mm/day. Figure 2i-j show that the rainfall induced by typhoon Neoguri and Matmo was stronger on the left-hand side of the track than on the righthand side, which coincides with the findings of previous studies [46][47][48][49]. However, the subsequent typhoons, Nakri and Halong, induced a right-bias rainfall (Figure 2k-l), which was probably due to the asymmetrical precipitable water vapor distribution caused by the first two typhoons.…”
Section: Resultssupporting
confidence: 89%
“…Figure 2i-l show the rainfall distribution during the passage of sequential typhoons, and the maximum rainfall exceeded 200 mm/day. Figure 2i-j show that the rainfall induced by typhoon Neoguri and Matmo was stronger on the left-hand side of the track than on the righthand side, which coincides with the findings of previous studies [46][47][48][49]. However, the subsequent typhoons, Nakri and Halong, induced a right-bias rainfall (Figure 2k-l), which was probably due to the asymmetrical precipitable water vapor distribution caused by the first two typhoons.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies confirmed that TC landfall impacts (e.g. rainfall and wind) are affected by TC characteristics including track direction (Lee et al ., 2006; Chan et al ., 2019), intensity (Emanuel, 2005; Yu et al ., 2017), size (Matyas, 2006; Chen et al ., 2011), translation speed (Su et al ., 2012; Hsu et al ., 2013), duration (Done et al ., 2018), asymmetric structure (Lonfat et al ., 2004; Chen et al ., 2016), as well as interactions among these characteristics (Teng et al ., 2020a). Landfall impacts are also affected by the interaction of TCs with the land surface, causing phase‐locked wind and rainfall patterns (Chang et al ., 1993; Lin et al ., 2001; Chiao and Lin, 2003; Hsu et al ., 2013; Lu et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetries in the TC rainfall associated with landfalling can be modulated by not only VWS [30][31][32][33][34], but also some other factors, such as nonuniform surface features including land-sea contrast and local topographic effect [31,32,[34][35][36][37][38][39] and interaction between TCs and synoptic weather systems [38,40,41]. In general, the landfalling TCs regularly had an asymmetry with a downshear to downshear-left rainfall maximum near the coastal regions, which is consistent with the studies for TCs over the ocean [3,19,42].…”
Section: Introductionmentioning
confidence: 61%